FERMENTASI HIJAUAN SEBAGAI PAKAN ALTERNATIF BERKUALITAS UNTUK TERNAK - Syamsuria; Andi Srimularahmah; Trisna Dayanti; Andi Paradilla Astifa; Ika Sulistiawati; Winda Darwis; Haerul; Saldiawan; A. Angga Renaldy; Agus; Asrianto (BEGAWE: Jurnal Pengabdian Masyarakat, 2024)
Samaelo Village is one of the villages in Bone Regency, South Sulawesi. Which has quite extensive rice farming land. The abundant rice farming results have their own impacts in the form of accumulation of rice straw waste. Rice straw waste is usually burned when it is dry or left to rot. The way rice straw waste is managed has caused air and water pollution due to smoke from burning or the smell of rotting rice straw. Therefore, to minimize pollution caused by rice straw waste, this activity aims to provide training in processing rice straw waste using fermentation techniques into animal feed to farmer and livestock groups in Samaelo Village. The method of implementing the activities includes observation, socialization, demonstration, and evaluation. Based on the results of the implementation of the activities, it is known that (1) the Samaelo village livestock group began to understand the benefits of using fermented straw as animal feed. (2) the livestock group began to be interested in making and trying to provide the results of fermented straw processing to livestock.